Collaborative Learning to Advance Knowledge and Implementation of Strategic Health Purchasing in Sub-Saharan Africa. Issue 2 (1st March 2022) - Gatome-Munyua, Agnes; Tapsoba, Charlemagne; Cashin, Cheryl
ABSTRACT: Strategic purchasing means deliberately directing health funds to priority populations, interventions, and services. This is done by actively creating incentives so funding is used equitably and efficiently and is aligned with population health needs. Strategic purchasing is a complex policy area fraught with challenging technical, institutional, and political issues. Policy makers and practitioners are an important source of tacit knowledge—experiential knowledge that is context specific and gained over time. Collaborative learning, through which a group of peers jointly problem-solves and generates lessons and solutions that can be adapted to different country contexts, is an important way to advance collective understanding of how to make progress on strategic purchasing within the unique health financing systems of sub-Saharan Africa. The Strategic Purchasing Africa Resource Center (SPARC), a resource hub hosted by AMREF Health Africa with technical support from Results for Development, is facilitating a collaborative learning agenda among 11 technical partners in 10 countries. SPARC and the technical partners are generating new insights and practical lessons to inform country policy and regional discourse on how to better use strategic purchasing to advance progress toward universal health coverage (UHC). This paper summarizes lessons and best practices from SPARC's collaborative learning approach that can benefit others who are seeking to apply a similar approach to share tacit learning on strategic purchasing and UHC.